2018
DOI: 10.1111/1440-1681.13030
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory cytokines tumour necrosis factor‐α and interleukin‐8 enhance airway smooth muscle contraction by increasing L‐type Ca2+ channel expression

Abstract: Inflammation elevates intracellular calcium concentrations ([Ca ] ) in airway smooth muscle (ASM). The L-type Ca channel (L-VDCC) plays an important role in regulating Ca influx in ASM. However, the role of L-VDCC in the inflammatory cytokine-induced pathology of ASM remains unclear. In the present study, we used calcium imaging and isometric tension measurements to assess the role of L-VDCC in agonist-induced [Ca ] rise and the associated contractions in mouse ASM, and we used immunoblotting to identify L-VDC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The RT-PCR results showed that the increased expression levels of TNF, Muc5ac, IL-4, IL-13, and IL-12b in asthmatic mice was significantly reduced in diacerein-treated mice, which elucidated that diacerein might provide anti-inflammatory benefit via reducing these inflammatory mediators. Besides that, previous study also demonstrated that inflammatory cytokines might enhance ASM contraction by increasing expressions of certain ion channels and elevating intracellular calcium concentrations (Ding et al, 2019), which implied that the anti-contractile feature of diacerein might also benefit from down-regulated inflammatory mediators. However, more experiments need to be conducted to confirm it.…”
Section: Discussionmentioning
confidence: 86%
“…The RT-PCR results showed that the increased expression levels of TNF, Muc5ac, IL-4, IL-13, and IL-12b in asthmatic mice was significantly reduced in diacerein-treated mice, which elucidated that diacerein might provide anti-inflammatory benefit via reducing these inflammatory mediators. Besides that, previous study also demonstrated that inflammatory cytokines might enhance ASM contraction by increasing expressions of certain ion channels and elevating intracellular calcium concentrations (Ding et al, 2019), which implied that the anti-contractile feature of diacerein might also benefit from down-regulated inflammatory mediators. However, more experiments need to be conducted to confirm it.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, this behavior differs from that observed in 3D-bioengineered C2C12 cells, which only show a sustained tetanic contraction for frequencies higher than 10 Hz without an initial stroke 2 . TNF-α is a proinflammatory cytokine known to be related to sarcopenia, or loss of muscle mass and function in ageing, as well as reduction of cell fusion [25][26][27][28][29][30][31] . Hence, we examined whether addition of this cytokine could be used to model aged skeletal muscle tissue in our muscle platform.…”
Section: Resultsmentioning
confidence: 99%
“…This cytokine has been described as one of the main drivers for the known morphological changes that take place in senescent muscles [23][24][25] , and has been linked to the development of sarcopenia affecting satellite cells 26 . In mouse cell lines, differences in TNF-α have been related to changes in calcium transients 27,28 and reduction of contractile force 25 . Furthermore, in vitro, this cytokine is known to have an effect on myogenesis inhibition 29 and cause atrophy 30 , as demonstrated in C2C12 cell lines, as well as having an important effect in muscle regeneration after injury in vivo 31 .…”
Section: Introductionmentioning
confidence: 99%
“…histamine, bradykinin, and LTs), which have been reported to contribute to SARS-CoV-2induced inflammation. 4 A major consideration is that several of the pro-inflammatory mediators released by effector cells in COVID-19 act on airway smooth muscle cells and induce bronchoconstriction, 4,27,28 which can be relieved by (combined) PDE3-inhibitors producing (potent and sustained) bronchodilation. 5,[7][8][9][10]21 Recently, based on their broad anti-inflammatory activity, systemic corticosteroids have been advocated in severe COVID-19 patients requiring supplemental oxygen (i.e., with a similar indication as our COVID-19 cases) in line with the preliminary findings in the RECOVERY study.…”
Section: Discussionmentioning
confidence: 99%